International Monetary Fund Annual Report 2014 : Financial Statements. - International Monetary Fund. Secretary's Department (Washington, D.C. : International Monetary Fund, 2014)
This companion volume to the International Monetary Fund's Annual Report 2014-From Stabilization to Sustainable Growth contains the audited financial statements that form Appendix VI to the report. The financial statements can also be found, together with Appendixes I through V and other materials, on the Annual Report 2014 web page (www.imf.org/external/pubs/ft/ar/2014/eng).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet